Anomalously persistent p-type behavior of WSe2 field-effect transistors by oxidized edge-induced Fermi-level pinning. Issue 3 (5th January 2022) - Ngo, Tien Dat; Choi, Min Sup; Lee, Myeongjin; Ali, Fida; Yoo, Won Jong
Abstract : Strong Fermi-level pinning is observed in WSe2 devices with edge contacts due to the presence of an oxide layer at the etched interface. Abstract : A technique to form the edge contact in two-dimensional (2D) field-effect transistors (FETs) has been intensively studied for the purpose of achieving high mobility and also recently overcoming Fermi-level pinning (FLP). However, most of the previous studies on the effects of edge contact have been conducted mainly on graphene and molybdenum disulfide (MoS2 ) until now. Here, we report an anomalous electrical transport of edge-contacted WSe2 FETs that is different from the typical Fermi-level depinning behavior in MoS2 FETs reported previously. Such WSe2 FETs showed a consistent p-type behavior regardless of contacting metals including low work-function chromium and indium and high work-function palladium, with a small pinning factor of 0.04. It suggests a strong FLP near the valence band edge of WSe2 . The cross-sectional high-resolution transmission electron microscopy and energy-dispersive X-ray spectroscopy analyses revealed the formation of an oxide after plasma etching at the interfacing edge near the metallic contact, which was found to be responsible for the strong FLP. The temperature dependent electrical characteristics of the device indicated the occurrence of Fowler–Nordheim tunneling with high electrical biases, further supporting the presence of an oxide at the contact edge of WSe2 . Interestingly, the oxide was removed upon wet treatment in potassium hydroxide, which could be an effective way to control carrier polarity by suppressing the FLP. This work provides a new insight into the impact of edge contacts on surface sensitive 2D materials.